Hysteric Subject between the Imaginary and Symbolic Orders: A Lacanian Critique of Curfewed Night - Sabir Hussain; Dr. Ali Usman Saleem (Journal of Management Practices, Humanities and Social Sciences, 2022)
This research attempts to unearth the contrasting discourses that constitute the subjectivity in Basharat Peer’s memoir. By highlighting the circulation of these multiple discourses, the research further endeavours to trace the resistance in the subject's agency. These discourses, often resorting to violent modes of disciplining, relentlessly struggle to configure the subject. However, with its potential for resistance, the subject's agency subverts all these hegemonic configurations. Drawing upon Lacan's imagery and symbolic orders along with Lacanian discourses: master's discourse, university's discourse, analyst's discourse, and hysteric's discourse, this paper reads the incidents as symptomatic of a problem beyond their literal signification. This paper concludes that the Kashmiri subject becomes a battleground for these contradictory forces: the military and the militants. However, their modes of fashioning and disciplining the subject go awry with the agency's resistance.